Evaluation of the acoustics performance of the KAED main auditorium - Nik Mohammad Aimaq (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2021)
The main auditorium in the Kulliyyah of Architecture and Environmental Design (KAED) serves as a vital venue, functioning as a multi-functional hall. However, acoustic quality is the main issue challenging the KAED Main Auditorium. The current acoustics performance of the KAED Hall is not desirable as a multi-functional space. There are many significant contributors to the acoustic quality of the KAED Main Auditorium, such as undesirable acoustic design, unpleasant geometric shape, wrong reverberation time, uneven distribution of sound, and physical performance of the hall. Moreover, there are several other causes like surface finishing, lack of diffusers, the layout of the boundary surface (balanced horizontal ceiling and concave wall), seating cloth, and stage wall that further contribute to the auditorium’s poor acoustic quality. All of these factors reduce the intelligibility of speech. In addition, they cause poor communication between speakers and audiences in some parts of the space, such as rear rows and the centre-back area of the auditorium. Thus, students may get fewer benefits from lectures held there, which subsequently affects the students’ educational quality. This research, which is presented as a dissertation, studies the aspect of acoustic quality (causes, effects, and preventive strategies) of the KAED Main Auditorium to evaluate its acoustics performance. The main agenda is to identify a viable solution to the acoustic issue of the multi-purpose auditorium. For this purpose, data were processed and evaluated in two stages. The first stage involved three types of survey measurements on the acoustic quality of the site. The first of the three was a sound level reading by the sound meter, the second involved identification of the areas and volume of the KAED Main Auditorium (i.e., approximately about 620 square meters and 3141.23 cubic meters, respectively), and the third measurement was designed to examine the absorption of each surface finishing. The second stage was a survey questionnaire to 50 students at the Kulliyyah of Architecture and Environmental Design. The result and findings are explained and analysed by figures, drawings, tables, and column graphs. Eventually, the research forwards several recommendations to improve the acoustic performance of the KAED Main Auditorium.